Micropezidae (Diptera, Nerioidea) of Mauritius, with a description of Paraeurybata new genus - Marshall, S.a. (Zootaxa, 2019)
The Micropezidae species of Mauritius are reviewed on the basis of recent collections. Mimegralla splendens (Wiedemann 1830) is newly recorded from Mauritius and the new genus Paraeurybata is described for Calobata taeniata Macquart 1851. A third species, Courtoisia apicalis (Macquart 1851), remains known only from the type specimen collected in Réunion and from a single specimen collected in Mauritius in 1963.